Systematic position of the monotypic Azorean genus Falbouria Dyte with notes on the definition of Chrysotus Meigen (Diptera: Dolichopodidae) - Capellari, Renato Soares; de Souza Amorim, Dalton (Zootaxa, 2012)
The systematic position and the generic status of the monotypic genus Falbouria Dyte (Dolichopodidae: Diaphorinae) are evaluated. The type-species of the genus, F. acorensis (Parent), endemic to the Azores, is re-described, and hypopygial and oviscapt morphology illustrated in detail for the first time. Falbouria is kept as a separate genus, but close to Chrysotus Meigen, which is certainly paraphyletic (or even polyphyletic) in its present composition. A brief discussion on the delimitation of Chrysotus is provided and its laesus-group of species is suggested as the core clade of the genus.